Design and development of a digging device for harvesting sweet potato - Hamid, Md. Akhir (2010)
This thesis describes a study on the design, fabrication and testing of a prototype sweet potato digging device for harvesting sweet potato tubers in bris soil. Design of the digging device was based on a soil bin study having bris soil with mean moisture content of 9.16% wet basis. The soil texture was sandy soil (fine sand 94.53%), and the mean bulk density of soil was 1.44 g-cm-3. Three types of soil digging tools were designed and fabricated to determine the optimum draft force. These were plane, V-shaped and Hoe type blades. Plane and V-shaped blades were 30 cm long, and 13 cm wide, while the Hoe type had three rods, 25 mm diameter, 30 cm long and 6.5 cm wide with sharp cutting edge. The digging tools were tested in a soil bin filled with bris soil to determine the optimum draft force. The experiments were conducted at three depths and rake angles. All experiments were replicated three times at a constant speed of 0.06 m.s-1. The results from this study were analysed and the best type was selected, fabricated and used as the prototype harvesting device. Analysis of variance (ANOVA) for all blade types and rake angle show that, there were no significant differences between blade type and rake angle on draft force, vertical force, moment and area of soil disturbance. Comparison between all blade types and blade depths to measured draft force and area of soil disturbance showed that the highest draft of 0.54 kN was caused by plane blade at the optimum depth of 20 cm with 0.180 m2 of soil disturbance area. The V- shaped blade had the mean draft of 0.51 kN at the optimum depth of 20 cm. The area of soil disturbance was 0.185 m2. The best choice was V-shaped blade with rake angle of 30o at depth of 20 cm. The hoe-type tool had a mean draft of 0.34 kN and soil disturbance area of 0.184 m2. The hoe-type was not selected because of excessive damage to tubers. Based on the above information a double row sweet potato harvesting device was designed and developed. The machine was designed and developed at the Mechanization and Automation Centre, Malaysian Agricultural and Development Research Institute (MARDI) workshop. The machine consists of digger blades, double disc coulter for cutting vines, digger blade guide, and adjustable drum for blade digger depth control during operation, conveyor lifter, conveyor separator and bucket collector. Digging blade depth is adjustable with common hand tools. The harvester was designed to be pulled by Standard Four–wheel tractor of 70 HP or larger. The tractor power requirement was estimated by Algorithm analysis and tool draft force predicted by Hettiaratchi and Reece’s model. Under normal operation, the machine requires three persons; one tractor driver and labourers on the harvester platform to collect the sweet potato tubers. The machine was tested on bris soil at Mardi Station, Telong, Kelantan. The digger blade was set at 35 cm depth since the average tuber zone depth was 30 cm, tractor engine speed between 1700 – 2000 rpm and PTO speed setting at 540 rpm during operation. The mean effective work of the machine in bris soil was 93.64 and 90.49% for Telong and VitAto varieties respectively. The average ground speed and turning time during operation was 0.56 km-hr-1 and 102.7 s and 0.99 km-hr-1 and 81.22 s for plots A and B respectively. The different results in tractor speed and turning for both plots were due to the different drivers operating the prototype machines. Other factors include the difference of plot size. Plot A had 50 m long seedbed while Plot B, 70 m. The harvesting efficiencies for both plots were above 90% and show no significant difference. The total productive time (harvesting time) and unproductive time (turning time) in plot A, with tractor speed 0.56 km-hr-1, was 14.8 hours for harvesting a hectare of sweet potato ( 0.068 ha-hr-1). In plot B, the total time for harvesting a hectare of sweet potato was 8.35 hours (0.12 ha-hr-1) with tractor speed of 0.99 km-hr-1. The average harvesting time for both plots was 11.47 hr- ha-1. The average field work rate was 0.087 ha-hr-1 or 34 man-hr-ha-1 compared to manual harvesting of 150 man hr-ha-1.